Pengaruh Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan PT. Mackessen Indonesia - Putra, Bagas Pratama; Sunarsih, Denok (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2023)
This study aims to analyze the effect of communication and work discipline on the performance of PT Mackessen Indonesia) employees. The research method used in this research is quantitative research. The sample used in this study is the result of the slovin technique, namely 61 respondents. Data analysis used the SPSS version 25 program. The analysis techniques used were data instrument testing, classical assumption testing, analysis testing and hypothesis testing. Testing the hypothesis partially on the communication variable (X1) obtained the value of tcount > ttable (2.716 > 1.671) and a significance value of 0.009 > 0.05. This means that communication (X1) has a significant effect on employee performance (Y). Statistical test of work discipline variable (X2) on employee performance obtained tcount > ttable (5,280 > 1.671) and a significant value of 0.000 <0.05. This means that work discipline (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained fcount > ftable (50,709 > 3.153) and a significance value of 0.000 <0.05. So it can be concluded that communication (X1) and work discipline (X2) have a significant effect simultaneously on employee performance (Y). The determination obtained by R Square is 0.111, meaning that the communication and work discipline variables together have an influence contribution of 88.9% on employee performance. While the remaining 11.1% is influenced by other factors not examined in this study.